THEORETICAL BASES FOR BANK STRATEGIC RISK MANAGEMENT UNDER THE IMPACT OF MACRO- AND MICROENVIRONMENT (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Purpose of research. The purpose of this research is to examine the theoretical bases for banking strategic risks management through examining the impact of micro- and macroenvironment on the credit performance. . Research method. The authors of this research used such methods as: research and analysis of legal framework, study of In this study, the authors have used such methods of scientific research as the study and analysis of the regulatory framework , the study of monographic publications and articles, analysis. Results. The authors propose to specify the notion of strategic management. Thus the principles of strategic management were developed and specific characteristics of commercial banks financial management have been defined. Besides that the notion of financial risk of the credit organization was specified and new approach to commercial banks’ risk management, based on their origin was developed.Implementation of the results. The results can be used for the publications on different aspects of this topic and in the educational process of the education institutions. Theoretical aspects connected to the difficulty of evaluating banking risks and described in the paper, can be of interest in the process of developing practical measures on preventing or minimizing extent of exposure of the banking system to the risks in general.The main concepts of this research can become a base for further scientific and practical research in the field of rationalizing the banking risks management system.